Entrepreneurship education perceptions of undergraduate students in Medellin: A case study (2015)
The higher education institutions in their quest to promoting entrepreneurship in their students have implemented various strategies aimed to strengthen the entrepreneurial skills and preparation of potential entrepreneurs. However, there are still few studies focused on the perceptions and expectations of university students and the educational strategies for entrepreneurship implemented in their universities, which it is necessary to propose studies that allow detecting the needs of entrepreneurship training identified by students. Considering the need previously mentioned, this exploratory study is presented to examine the perceptions of university students from the Economics and Administrative Sciences Departments of Instituto Tecnológico Metropolitano, Corporación Universitaria Minuto de Dios and Universidad de Medellin, about educational strategies for entrepreneurship implemented in their respective institutions. The methodology applied is quantitative approach through the application of a self-administered questionnaire to 209 undergraduate students. Among the results, it is observed that most students consider that they require a larger training in entrepreneurship. Furthermore, they have a high level of interest to take courses related to business creation. In addition, the most frequently source reasons to not create a business by them are: not having a business idea, low economic resources and feel unprepared to create an enterprise. © The Turkish Online Journal of Educational Technology.